Escolarização e inclusão de alunos indígenas com deficiências nas escolas indígenas de São Félix do Xingu - PA - Ribeiro, Nádia Fernandes (2023)
This work aims to present a concise description of the history, characteristics, legislation and process of inclusion and schooling of indigenous students, besides to understand the educational strategies aimed at the schooling of Mebêngôkre (Kayapó) students with disabilities in regular education, at São Félix do Xingu, Pará. We identified and carried out the diagnosis of the students in different communities. To carry out this dissertation, primary data were collected from the students and from the observations made during two years acting as coordinator in indigenous schools.